Preconcentration of diluted mixed-species samples following separation and collection in a micro–nanofluidic device - Chen, Yi-Ying (Biomicrofluidics, 2016)
A microfluidic device consisting of a nanoscale Nafion membrane and a polydimethylsiloxane microchannel is proposed for the preconcentration of diluted multi-mixed species samples then following separation and collection. When an electric field is applied across the microchip, an accumulation of the mixed-species sample occurs at the junction between the microchannel and the membrane by means of ion concentration polarization effect. A separation of the sample then takes place due to the difference in the electrophoretic mobilities of the sample components. Finally, the component of interest is guided to a collection reservoir by manipulating the external potential configuration and is trapped in place by means of a magnetically actuated valve. The preconcentration performance of the proposed device is evaluated in both straight and convergent microchannels using a fluorescein isothiocyanate labeled bovine serum albumin (FITC-BSA) sample. It is shown that a preconcentration factor of 40 times can be achieved using a straight microchannel. By contrast, the preconcentration factor increases to 50 times when using a convergent channel. The practical feasibility of the proposed device is demonstrated by performing the preconcentration, separation, and collection of a mixed FITC-BSA and Tetramethylrhodamine sample.